Pricing product options and using them to complete markets for functions of two underlying asset prices - Dilip B. Madan; King Wang (Journal of Risk and Financial Management, 2021)
Options paying the product of put and/or call option payouts at different strikes on two underlying assets are observed to synthesize joint densities and replicate differentiable functions of two underlying asset prices. The pricing of such options is undertaken from three perspectives. The first perspective uses a geometric two-dimensional Brownian motion model. The second inverts two-dimensional characteristic functions. The third uses a bootstrapped physical measure to propose a risk charge minimizing hedge using options on the two underlying assets. The options are priced at the cost of the hedge plus the risk charge.
Keywords: G10; G11; G12; 330; acceptable risks; distorted expectations; fast Fourier transform; multivariate bilateral gamma